Evaluating the Predictive Power of the Fama-French Three-Factor Model in Islamic Capital Markets: Evidence from JII70 Stocks - Yasir Maulana; Munir Nur Komarudin; Nurul Siti Jahidah; Herma Wiharno (Universitas Alma Ata, 2025)
Introduction: Stock returns are a crucial aspect on forming portfolio investing. For investors, they serve as an indicator for measuring the level of profit or loss generated from an investment over a specific period. The purpose is to examine the applicability of the Fama-French Three-Factor Model in predicting excess returns for Jakarta Islamic Index (JII70) stocks within a Sharia-compliant equity universe.Method: We analyze JII70 stocks for the period 2019-2023. The Factors included are market risk premium, firm size proxied by SMB, and book-to-market proxied by HML. Building a portfolio, SMB, and HML, and analyzing it with data panel regression. After the portfolio was built, the factor analysis was conducted by ordinary least squares regression using risk, size, and book-to-market factors on Fama-French Model.Results: The results reveal that only the book-to-market factor (HML) consistently and significantly influences excess stock returns. In contrast, the market risk premium and size factor do not show meaningful effects across the sample. These findings indicate that value-related characteristics still play a role in Islamic stock pricing, whereas risk and size dimensions may behave differently due to Sharia screening.Conclusion: The model's predictive power is weak in Islamic markets, implying the need for additional factors. Suggests refinement of Islamic asset pricing frameworks. Investors and portfolio managers in Indonesia's Islamic capital market should integrate additional factors such as momentum, liquidity, or ESG to enhance predictive accuracy. The unique characteristics of Sharia-compliant stocks necessitate tailored asset pricing models, while regulators can use these insights to refine Sharia index methodologies.